Flowers - Burnie, David; Gedye, Jane (New York : DK Pub., 1997)
A young explorer's guide to flowers, discussing their different parts, their purpose, and how they bloom; looking at color and scent; examining different types of flowers and seeds; and including suggestions for flower-related projects and observations.
Includes index.
Appraisal-Science Books for Young People.
L.A. Recommended Foreign Language.
Library Talk.
3.8.
3.8
Keywords: Flowers -- Juvenile literature; Wild flowers -- Juvenile literature; Flowers; Wild flowers; Flowers; Wild flowers